PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, KERJASAMA TIM, DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN WARUNG MINA CABANG RENON - Natalia Tailan; Anak Agung Dwi Widyani; Ni Made Satya Utami (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2021)
Employee performance is how much the employee contributes to the organization, namely quantity, quality, duration of output and the level of absenteeism at work as well as cooperation. In order for employees to provide good performance for the company, companies need to pay attention to all factors that affect employee performance. This study aims to analyze the effect of transformational leadership style, teamwork and communication on employee performance at Warung Mina, Renon Branch in Denpasar. This study uses the entire population as respondents, namely 55 people who are registered as employees of Warung Mina, Renon Branch. Data were collected by observation, interviews and questionnaires. The analysis technique used is multiple linear regression analysis techniques. The results of hypothesis testing show that all the proposed hypotheses are accepted. Transformational leadership style has a positive and significant effect on employee performance. Teamwork has a positive and significant effect on employee performance. Communication has a positive and significant effect on employee performance.